Mediating Speech Actions of an Adult in Telling a Story by a Child: Hypothesis about the Interactive Nature of Narration in a Child’s Speech Activity - N. M. Yurieva (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The role and functional purpose of the statements of an adult in telling a story by children is considered. The relevance of the study is due to the following: in the theory of speech ontogenesis, the formation of a narrative is  associated to a greater extent with the assimilation of linguistic means by children, the improvement of syntax and syntactic structures, while modern linguistics emphasizes the importance of another component — the cognitive and reflective side of this process, which determines the plot complexity, multilayer and the integrity of the story being told. The novelty of the research is seen in the fact that the idea of the action of the interactive component in telling a story by children is confirmed by new empirical data and receives theoretical understanding based on the cognitive-discursive approach developed by modern science. An attempt was made to expand the understanding of the influence of an adult on a child’s telling a story, to highlight different forms of mediating actions of an adult in the course of this process. The concept of interactive converting narrative, which is interpreted as one of the subspecies of converting narrative, is explained. It is shown that the mediating actions of an adult through interrogative statements interfere with the child’s mental activity, directing attention to the structure of episodes in history, highlighting the main characteristics of each episode in accordance with the logic of the participants’ actions in specific episodes.